(untitled) (Journal of Applied Oral Science, 2015)
Detection of abnormally elevated levels of molecules in patients with oral cancer may be useful in early diagnosis. These markers can be included in current Histopathology grading and in TNM staging systems of Oral Squamous Cell Carcinoma (OSCC) to make it more efficient. Several pro-angiogenic molecules have been assessed for the same reason. Endothelin-1 (ET-1) is a vasoactive peptide associated with the development and spread of many solid tumors, including Squamous Cell Carcinoma (SCC), but its utility in OSCC has not been confirmed.Objective This study aims to evaluate the role of the serum big ET-1 as a biomarker of OSCC, by correlating it with the clinical staging and the histopathological grading.Material and Methods Serum levels of big ET-1 measured by the sandwich Enzyme-Linked Immunosorbent Assay (ELISA) in 40 OSCC cases were compared with the levels from the control group using independent t-test. Clinical stages and histopathological grades of OSCC cases were compared in relation to their mean levels of serum big ET-1, one using the Analysis of Variance (ANOVA) test and the other the independent t-test, respectively. The significance of the mean difference between the groups was evaluated by Tukey’s multiple comparison test. All statistical analyses were performed on GraphPad statistical software version 5.0.Results By comparing the mean of the big ET-1 concentrations of cases and controls, the independent t-test revealed significant higher big ET-1 concentration of OSCC cases when compared to controls (p